Brazilian Lesbian Webseries as a Transgression Product - Trigueiro Moura, Vanessa Paula (2023)
Webseries are serial narratives, similar to television series, that emerge from the context of convergence culture and are produced for distribution on the web. In this context, the article proposes a reflection on the prohibition in the regime of representation of gender and sexuality in Brazilian soap operas and a debate on lesbian webseries, introducing the concept of escape applied to these fictional narratives. It starts from the idea that webseries inaugurate new visibilities and break with patterns guided by heteronormativity. Finally, we present the universe of these productions in Brazil, bringing the webserie SEPTO as a representative of these narratives.